2022
DOI: 10.48550/arxiv.2203.03658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular gas in z~6 quasar host galaxies

Roberto Decarli,
Antonio Pensabene,
Bram Venemans
et al.

Abstract: We investigate the molecular gas content of z ∼ 6 quasar host galaxies using the Institut de Radioastronomie Millimétrique / Northern Extended Millimeter Array. We target the 3 mm dust continuum, and the line emission from CO(6-5), CO(7-6), [C i] 2−1 in 10 infrared-luminous quasars that have been previously studied in their 1 mm dust continuum and [C ii] line emission. We detect CO(7-6) at various degrees of significance in all the targeted sources, thus doubling the number of such detections in z ∼ 6 quasars.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…The resulting gas  and   of our quasars at their respective dyn  are shown in Figure 1 (left panel). The gas mass is distributed between ∼10 10 -10 11 M e , which is consistent with recent direct measurements in z ∼ 6 quasars (e.g., Decarli et al 2022). The derived   is typically 0.2-0.5 dex smaller than dyn  .…”
Section: Samplesupporting
confidence: 89%
See 1 more Smart Citation
“…The resulting gas  and   of our quasars at their respective dyn  are shown in Figure 1 (left panel). The gas mass is distributed between ∼10 10 -10 11 M e , which is consistent with recent direct measurements in z ∼ 6 quasars (e.g., Decarli et al 2022). The derived   is typically 0.2-0.5 dex smaller than dyn  .…”
Section: Samplesupporting
confidence: 89%
“…This gives rise to a luminosity-dependent virial BH mass bias (hereafter the SE bias) as detailed in Shen (2013). In addition, the hosts of z ∼ 6 quasars are found to be gas rich (e.g., Decarli et al 2022), thus approximating   by dyn  is likely an overestimate. In this Letter, we model the selection and measurement biases for a z ∼ 6 quasar sample compiled in the literature in order to reveal the underlying connection between SMBH and galaxy growth in the early universe.…”
Section: Introductionmentioning
confidence: 99%
“…Meijerink et al 2007). The observations of [CI] and [CII] emission lines in radio-quiet quasars point to the PDR origin of their [CII] emission (Venemans et al 2017;Novak et al 2019;Pensabene et al 2021;Meyer et al 2022;Decarli et al 2022), but the [CI] emission line has not yet been observed for any of the quasars in our sample.…”
Section: The Effects Of the Jet On Star Formationmentioning
confidence: 61%
“…We note that in deriving SFRs, we assumed that [CII] and IR luminosities are only related to the star formation in the host galaxies. This is a reasonable assumption for radio-quiet quasars at z 6 (Venemans et al 2017;Novak et al 2019;Pensabene et al 2021;Meyer et al 2022;Decarli et al 2022), but has not yet been tested for radio-loud ones. If AGN-related sources of [CII] and IR emission are significant, we are overestimating the SFRs.…”
Section: The Effects Of the Jet On Star Formationmentioning
confidence: 99%

The [CII] and FIR properties of z>6 radio-loud quasars

Khusanova,
Bañados,
Mazzucchelli
et al. 2022
Preprint
Self Cite
“…For instance, the M BH of flux-limited quasar sample might be systematically overestimated by the single-epoch virial estimator (e.g., Vestergaard & Osmer 2009; hereafter VO09) because of uncorrelated variation between AGN luminosity and broad line width (especially for Mg II and C IV) that gives rise to a luminosity-dependent virial BH mass bias (hereafter the SE bias) as detailed in Shen (2013). In addition, the hosts of z ∼ 6 quasars are found to be gas-rich (e.g., Decarli et al 2022), thus approximating M by M dyn is likely an overestimate.…”
Section: Introductionmentioning
confidence: 99%